To operate or not to operate? The impact of surgical treatment on quality of life in women with ovarian endometriosis - Spagnolo, Emanuela; Ramiro-Cortijo, David; Díaz Fuentes, Blanca; Suarez Vega, María; Calvillo-Fernández, Lucía; López, Ana; Hernández, Alicia (Frontiers in Global Women's Health, 2025)
BackgroundEndometriosis is a chronic gynecological condition that impacts on women's health, reducing their quality of life. Ovarian endometriosis (OE) and deep endometriosis (DE) are the primary manifestations. While surgical intervention in OE is common, its effects on quality of life remain debated. This study aims to assess global health perception and quality of life in women with OE with and without surgery to inform targeted interventions strategies.MethodsThis cross-sectional observational study was conducted at Hospital Universitario La Paz (Spain) and included women aged 25–55 diagnosed with OE, operated (OE-S) or not (OE-NS), as well as those with DE who had surgical resection. Women without endometriosis (control) was also included. Health-related quality of life was measured by SF-36, while pain perception, social support, and endometriosis-specific quality of life were assessed through validated instruments.ResultsRegarding global health, physical and social functions, emotional role, body pain, and global mental health did not find difference between groups. However, women with DE and OE-NS had significantly lower physical role and global health scores compared to controls. Vitality and physical component scores were lower in DE, while pain sensitivity was higher in OE-NS and DE. Social support perception was reduced in women with OE compared to controls. Quality of life was significantly lower in DE and OE-NS groups, with OE-S showing intermediate scores. Psychological well-being and endometriosis-related support were significantly low across all endometriosis groups. Sexual and occupational functions were higher in OE- S than in OE- NS and DE. Reproductive function was impaired in OE- NS compared to controls, while menstrual characteristics were significantly altered in all endometriosis groups. OE- S exhibited intermediate health and quality of life patterns between control and DE groups, whereas OE- NS was more similar to DE.ConclusionPsychological well-being and social support are reduced in all endometriosis groups, but surgical treatment in women with ovarian endometriosis preserve vitality, sexual, and occupational functions. A multidisciplinary approach is essential to improve quality of life in women with endometriosis.